SISTEM INFORMASI MANAJEMEN PENDIDIKAN BIMBINGAN BELAJAR BAHASA ASING LBPP LIA DALAM MEMPERTAHANKAN EKSISTENSI DI KOTA PEKANBARU - Gerian Anhar; Rusmadi Auza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
In the world of education, where the information system is one component that can not be separated from the educational activity itself. These two domains have a high enough level of dependency in shaping the characteristics of the educational world. Management in describing the relationship between both these aspects where education as a driver (drive) on the education information system, whereas the information system of education will be the determinant of educational performance. In this case there is a perspective view that education and information systems are in the micro-environment education institutions, is also a part of the macro world of education as a whole, the institution which has had a particular market segment endlessly improve the quality of its services education services served more competitive. It is undeniable that the development of information technology so quickly not only changed the way people communicate.The method used in this research is qualitative method. Data collection techniques in this study using interviews. The location of this research will be conducted at LIA LBPP Jalan Ahmad Yani No 23, Sukajadi, Pekanbaru. Subjects in this study is a miraculous administrators and Alumni LBPP LIA LIA, while objects in the study in this research is the role of the Education Management Information System In Existence Maintain. For data analysis, researchers used a method of interactive analysis and Hubberman Miles. As for checking the validity of the data, researchers used data triangulation technique.The results in this study indicate the presence of Education Management Information System, Institute of Language Education Professionals (LBPP) LIA has felt some of the following benefits: First, the availability of data and information management system of education. Second, integration of data and educational information to support the decision-making process. Third, the availability of data and information on a complete education for all stakeholders to join in education The constraints faced by the Institute of Language Education Professionals (LBPP) LIA usually come from competitors of the old, which is a collection of educational institutions that offer education programs are relatively equal in the eyes of the public education service users. In principle technologies on the run to the same educational program is how to create an educational program that is affordable, the quality is good, and served on time.Keywords : SIM, Managemet, Information, Education.